Training teaching staff to facilitate spontaneous communication in children with autism: Adult Interactive Style Intervention (AISI). Issue 3 (20th May 2014) - Kossyvaki, Lila; Jones, Glenys; Guldberg, Karen
Abstract : Previous research has demonstrated that the way adults interact with children with autism can have a great impact on their spontaneous communication. However, to date, few studies have focused on modifying adults' behaviour and even fewer have been conducted in school settings which actively involve teaching staff in designing the intervention. The aims of this study were twofold: (1) to explore the extent to which staff were able to build on their good practice and alter their interactive style and (2) to then assess the effects of this change on children's communication. The study used an action research methodology and involved three members of staff and six children with autism. The staff and the researcher developed an Adult Interactive Style Intervention (AISI) in partnership. This was based on two theoretical models of child development and disability. Data were collected pre‐ and post‐intervention and at follow‐up (12 months after the end of the main study) to measure change. The results showed that staff considerably increased the number of times they used AISI principles post‐intervention and that this change had a significant impact on the children's spontaneous communication. All three staff took an active participatory role in the study which was considered a very positive and empowering experience.